Expression of TTF-1 and CK-7 in the Diagnosis of Pleural Effusion Cytology Suspected Lung Adencarcinoma - Patricia Diana Prasetiyo; Ika Pawitra; Indra Wijaya (Faculty of Medicine, Diponegoro University, 2015)
Background : Lung cancer is the mayor disease that cause death worldwide including Indonesia especially Nonsmall cell lung cancer (NSCLC) consisting of adenocarcinoma, squamus carcinoma (SqCCA) and large cell carcinoma. Incidency of lung adenocarcinoma continues to rise recently about 40% of all NSCLC.Methods : Descriptive observational study design. The study population included the patients who were hospitalized at Kariadi central hospital in Semarang and had thorax X-ray or CT scan of thorax with a diagnosis of suspected lung malignancy, at the period of January 2012 – 2013. The variables assessed are expression of TTF-1 and CK-7.Result : A total of 20 samples subjected to Pearson correlation test with result of p value = < 0,001 and r = 0,867. Presentation of the highest expression TTF-1 in the all study sample is Adenocarcinoma 73,3% and highest expression CK-7 is also Adenocarcinoma 68,6%.Conclusion : Immunocytochemistry of TTF-1 and CK-7 can be used to determine Adenocarcinoma malignancy on cytological sample of suspected malignant pleural effusion